Evaluation of the Lean Approach Implementation in Engineering Education - Amine Hadek; Soumia Bakkali; Souad Ajana (Ital Publication, 2023)
This study aims to study the benefits of lean approach implementation in engineering education in Morocco by using three concrete case studies to present a comparative analysis between situations with and without Lean approach deployment. The first project focuses on improving internet access. The second project aims to improve the conduct of practicum sessions. The third project aims to identify and improve the performance of the processes implemented in the student affairs department. In this research study, deductive methodology is followed, also called the